New Scottish Photography : A critical review of the work of seventeen photographers - Brittain, David; Stevenson, Sara; Scottish National Portrait Gallery, Edinburgh (Edinburgh : Trustees of the National Galleries of Scotland, 1990)
Baird, Jean ; Bates, Lorna ; Cattrell, Peter ; Charity, John ; Colvin, Calum ; Cooper, Thomas Joshua ; Finnemore, Peter ; Heyer, Annette ; Logan, Owen ; Malde, Pradip ; O'Donnell, Ron ; Palmer, Roger ; Simpson, Ronnie Scott ; Stirling, Ruth ; Taylor, John ; Wiener, Dandy ; Williams, David
New Scottish Photography : A critical review of the work of seventeen photographers, Scottish National Portrait Gallery, Edinburgh, 6 November 1990 to 16 January 1991
boek